Eucalyptus ESTs corresponding to the protoporphyrinogen IX oxidase enzyme related to the synthesis of heme, chlorophyll, and to the action of herbicides - Velini, Edivaldo Domingues [UNESP]; Trindade, Maria Lúcia Bueno [UNESP]; Alves, Elza [UNESP]; Catâneo, Ana Catarina [UNESP]; Marino, Celso Luis [UNESP]; de Godoy Maia, Ivan [UNESP]; Mori, Edson Seizo [UNESP]; Furtado, Edson Luiz [UNESP]; Guerrini, Iraê Amaral [UNESP]; Wilcken, Carlos Frederico [UNESP] (FapUNIFESP (SciELO), 2005)
This work was aimed at locating Eucalyptus ESTs corresponding to the PROTOX or PPO enzyme (Protoporphyrinogen IX oxidase, E.C. 1.3.3.4) directly related to resistance to herbicides that promote oxidative stress, changing the functionality of this enzyme. PROTOX, which is the site of action of diphenyl-ether (oxyfluorfen, lactofen, fomesafen), oxadiazole (oxadiazon and oxadiargyl), and aryl triazolinone (sulfentrazone and carfentrazone) herbicides, acts on the synthesis route of porphyrins which is associated with the production of chlorophyll a, catalases, and peroxidases. One cluster and one single read were located, with e-values better than e-70, associated to PROTOX. The alignment results between amino acid sequences indicated that this enzyme is adequately represented in the ESTs database of the FORESTs project. Copyright by the Brazilian Society of Genetics.
Keywords: Catalase; Eucalyptus; Herbicide; Peroxidase; Protoporphyrinogen IX oxidase; amino acid; catalase; chlorophyll; chlorophyll a; diphenyl ether; fomesafen; heme; herbicide; oxadiazole derivative; oxadiazon; peroxidase; porphyrin derivative; protoporphyrinogen oxidase; amino acid sequence; cluster analysis; controlled study; enzyme active site; enzyme localization; enzyme synthesis; expressed sequence tag; genetic database; nonhuman; nucleotide sequence; oxidative stress; protein function; sequence alignment